Physiological factors in drought tolerance of various Musa genotype - Ekanayake, I.J.; Ortíz, R.; Vuylsteke, D.R. (1995)
Cultivated plantains and bananas (Musa spp.) are important staple crops in the humid forest and midaltitude ecologies of sub-Saharan Africa. Their water requirement is relatively high and they are very sensitive to dry soil conditions, which greatly limits their range of cultivation. While long-term drought is generally not common in traditional cultivation areas, it is a potential threat for plantains in West Africa, particularly during the short dry season. In llTA's ongoing efforts to develop broadly adapted genotypes, the study reported here attempted to differentiate plantains, bananas, and their hybrid genotypes for drought tolerance, on the basis of a sampling protocol developed to distinguish physiological responses.